Analysis of Mercury Content in Bivalves in the Marine Waters around the Bone Bolango River Estuary - Bramantio Setiawan; Femy M Sahami; Miftahul Khair Kadim (The NIKe Journal, 2020)
This study aims to analyze the content of mercury (Hg) in Bivalve in the marine waters around the mouth of the Bone Bolango river, Gorontalo City. The method used in this research is descriptive method. Sampling was done by purposive sampling by dividing the research location into 3 stations, namely Station 1 (mouth of the Bone Bolango River) Station 2 (Kelurahan Tanjung Kramat) Station 3 (Kelurahan Leato Utara). Measurement of mercury content (Hg) was carried out at the Fishery Product Quality Testing and Development Center (BPPMHP) Gorontalo City, Gorontalo Province using the Atomic Absorption Spectrophotometer (AAS) analysis method. The results showed that, there were 3 types of bivalves found in the research location, namely Hiatula sp, Lionconcha sp, Tridacna sp. The results of the analysis of the mercury content in the Bivalve samples found at the research location have not exceeded the maximum contamination threshold allowed for consumption with values for Station 1 ranging from 0.7022 - 0.8949 ppm, Station 2 ranging from 0.2593 - 0.3852 ppm and Station 3 ranging from 0.0998 - 0.8056 ppm. Keywords: mercury; bivalve; estuary; Bone-bolango River.